Strategi Pengembangan Bioindustri Kopi-Sapi Berbasis Korporasi Petani di Kabupaten Rejang Lebong, Bengkulu - Afrizon Afrizon; Andi Ishak (Pusat Penelitian dan Pengembangan Perkebunan, 2019)
Farmer-Owned Enterprise (FOE) of Bukit Kaba Mandiri in Rejang Lebong Regency is one of the economic institutions that is beneficial for farmers to increase the productivity and efficiency of coffee and cattle integrated farming suitable for its regional potentials. However, FOE is still in constraints due to its lack of organizational management capability in developing the coffee-cattle bioindustry hence the research aimed to build a strategy in developing the FOE in coffee and cattle bioindustry. The study was conducted at FOE of Bukit Kaba Mandiri in Rejang Lebong Regency, Bengkulu, from January to October 2018. Focus Group Discussion (FGD) was carried out to collect data with 16 respondents and in-depth interviews with FOE administrators. Data collected included strengths, weaknesses, opportunities, and threats faced by FOE which were then analyzed using Strength, Weaknesses, Opportunities, Threats (SWOT) method to formulate an FOE development strategy. The strategy was then compiled based on priorities with Analytical Hierarchy Process (AHP). The results formulated three strategies, namely: (1) increasing production of quality feed to meet the needs of dairy cattle, (2) producing competitively priced compost from cow manure, and (3) establishing market partnerships with coffee exporters. Producing competitively priced compost from cow manure is the first priority that FOE needs to develop.